Ni/NiO and Cu-Ag nanoparticles obtained by Pechini’s method: synthesis and characterization (Superficies y Vacío, 2012)
In this paper we study the synthesis and characterization of nanoparticles of Ni/NiO and Cu-Ag obtained by Pechini route. Gel precursors were prepared and the molar ratio of citric acid to metal salts was varied in order to study its effect on the obtained materials. The gel precursors were calcined at temperatures between 350 and 450 ° C in air for different times. The structural and morphological characterization was performed by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The results of X-ray diffraction showed the formation of nanoparticles of different metals and its alloys. The obtained phases were controlled by temperature and time of calcination. Transmission electron microscopy micrographs showed that in general the particles obtained have a size less than 20 nm.